(untitled) (Theatrum historiae, 2016)
The article focuses on the Reformation of two Silesian towns – Krnov (Jägerndorf) and Cieszyn (Teschen) – and gives an idea of its going in the course of the 16th century. In the observed towns, it describes in what period of time and under what conditions the Reformation could develop. It also studies the influence of the individual princes, alternatively the relevant town councils, on the whole process and religious life in the towns, and their steps by which they influenced it. It does not omit the Catholic clergy and monastic orders either and deals with their status and destiny during the Reformation. On the basis of the comparison of the both towns, it describes and assesses the specifics of the Silesian Reformation.